Retraction notice to “Comprehensive review on toxic heavy metals in the aquatic system: sources, identification, treatment strategies, and health risk assessment” [Environ. Res. 258 (2024) 119440] - Panchamoorthy Saravanan; V. Saravanan; R. Rajeshkannan; G. Arnica; M. Rajasimman; Gurunathan Baskar; Arivalagan Pugazhendhi (Environmental Research, 2026)

Correction to: Granulopoietic Dysregulation in a Patient-Tailored Mouse Model of Barth Syndrome - Elizabeth A. Sierra Potchanant; Maegan L. Capitano; Donna M. Edwards; Baskar Ramdas; Scott Cooper; James Ropa; S. Louise Pay; Aditya Sheth; Paige L. Snider; Hilary J. Vernon; Ngoc-Tung Tran; Reuben Kapur; et al. (Stem Cell Reviews and Reports, 2026)

Granulopoietic Dysregulation in a Patient-Tailored Mouse Model of Barth Syndrome - Elizabeth A. Sierra Potchanant; Maegan L. Capitano; Donna M. Edwards; Baskar Ramdas; Scott Cooper; James Ropa; S. Louise Pay; Aditya Sheth; Paige L. Snider; Hilary J. Vernon; Ngoc-Tung Tran; Reuben Kapur; et al. (Stem Cell Reviews and Reports, 2025)
Barth syndrome (BTHS) is an X-linked recessive disorder characterized by cardiomyopathy, skeletal muscle myopathy and fatigue, growth restriction, and neutropenia. Neutropenia increases the risk of life-threatening bacterial infections, a major cause of death in individuals with BTHS. Currently, there is no curative treatment for BTHS or associated neutropenia. The development of therapeutic strategies to correct BTHS-associated neutropenia has been hindered by a limited understanding of the underlying molecular mechanisms involved. BTHS is caused by a mutation in the Tafazzin gene encoding a transacylase required for the maturation of cardiolipin, an inner mitochondrial membrane phospholipid crucial for mitochondrial structure and function. We introduced a BTHS patient’s point mutation ( TAZ D75H ) into the mouse Tafazzin enzyme’s critical acyltransferase site using CRISPR/Cas9 -mediated genome editing, resulting in a patient-tailored point mutant knock-in BTHS model ( Taz D75H ) that expresses a stable mutant Taz D75H protein lacking transacylase activity. Taz D75H mice were then used to investigate how loss of Tafazzin enzymatic activity impacts hematopoiesis. Male Taz D75H mice exhibited impaired granulopoiesis and neutropenia secondary to impaired function of hematopoietic progenitors. Furthermore, they demonstrated age-dependent neutrophil maturation impairment reflecting the variable neutropenia observed in BTHS patients. Additionally, male Taz D75H mice exhibit chronic lymphopenia that persists post Taz D75H bone marrow transplantation. Mechanistically, the TAZ D75H point mutation caused hematopoietic cell mitochondrial dysfunction in patient-derived immortalized TAZ D75H lymphoblasts, increasing reactive oxygen species production and mitochondrial membrane depolarization. Likewise, Cyclosporine A treatment rescued these mitochondrial phenotypes in vitro, confirming TAZ D75H mitochondrial dysfunction. Overall, our findings demonstrate that mitochondrial dysfunction secondary to TAFAZZIN loss of enzymatic function underlies BTHS-associated neutropenia and lymphopenia.

Identification of Yield Limiting Nutrients Through the Diagnosis and Recommendation Integrated System (DRIS) for Fruit Crops - T. Sherene Jenita Rajammal; M. R. Latha; M. Baskar; K. J. Jeyabaskaran (Applied Fruit Science, 2025)

Ternary Fe3O4-CeO2/g-C3N4 nanocomposite: A magnetically reclaimable, visible light-active catalyst for efficient degradation of bisphenol A - Hussein M. Elmehdi; Shamima Begum; Krithikadevi Ramachandran; Baskar Malathi; Kamrul Hasan; Raed A. Al-Qawasmeh; Ihsan A. Shehadi (Journal of Water Process Engineering, 2025)

Gold nanocluster-based biosensing for rapid detection of carbapenem-resistant organisms in bloodstream infections - Rahul Harikumar Lathakumari; Leela Kakithakara Vajravelu; Poornima Baskar Vimala; Vishnu Priya Panneerselvam; Dakshina M. Nair; Jayaprakash Thulukanam; Ashwin Kumar Narasimhan (World Journal of Microbiology and Biotechnology, 2025)

Transformative strategies for saline soil restoration: Harnessing halotolerant microorganisms and advanced technologies - S. Salma Santhosh; S. Meena; M. Baskar; S. Karthikeyan; C. Vanniarajan; T. Ramesh (World Journal of Microbiology and Biotechnology, 2025)

Evaluating the combined effect of copper slag and silica fume on the flexural performance of RC beams with sustainable fine aggregate substitutes - P. Manibalan; M. Selvaradjou; R. Baskar; D. Senthilvelan; S. Kesaven (Innovative Infrastructure Solutions, 2025)

Genomic adaptations of methicillin-resistant Staphylococcus aureus in healthcare environments - Vishnu Priya Panneerselvam; Leela Kagithakara Vajravelu; Jayaprakash Thulukanam; Rahul Harikumar Lathakumari; Poornima Baskar Vimala; Dakshina M. Nair (Ecological Genetics and Genomics, 2025)

Tackling hepatitis B Virus with CRISPR/Cas9: advances, challenges, and delivery strategies - Dakshina M. Nair; Leela Kakithakara Vajravelu; Jayaprakash Thulukanam; Vishnupriya Paneerselvam; Poornima Baskar Vimala; Rahul Harikumar Lathakumari (Virus Genes, 2024)

RETRACTED: Comprehensive review on toxic heavy metals in the aquatic system: sources, identification, treatment strategies, and health risk assessment - Panchamoorthy Saravanan; V. Saravanan; R. Rajeshkannan; G. Arnica; M. Rajasimman; Gurunathan Baskar; Arivalagan Pugazhendhi (Environmental Research, 2024)

Irrigation methods suitable for vegetable crops cultivation in sodic soil with alkaline irrigation water - M. Selvamurugan; P. Balasubramaniam; M. Baskar; A. Alagesan; M. J. Kaledhonkar (Paddy and Water Environment, 2024)

Status and future trends in wastewater management strategies using artificial intelligence and machine learning techniques - Gurunathan Baskar; Soghra Nashath Omer; Panchamoorthy Saravanan; R. Rajeshkannan; V. Saravanan; M. Rajasimman; Venkatkumar Shanmugam (Chemosphere, 2024)

Flexural behavior of RC beam using industrial copper slag as a sustainable substitute for fine aggregate - P. Manibalan; M. Selvaradjou; R. Baskar; G. Abirami (Innovative Infrastructure Solutions, 2024)

Native bio-control agents from the rice fields of Telangana, India: characterization and unveiling the potential against stem rot and false smut diseases of rice - Sowmya Vanama; N. S. Raja Gopalan; Maruthi Pesari; M. Baskar; Uma Devi Gali; D. Ladha Lakshmi; P. Koteshwar; G. Jesudasu; Santosha Rathod; M. Srinivas Prasad; Rajanikanth Panuganti; R. M. Sundaram; et al. (World Journal of Microbiology and Biotechnology, 2024)

Investigations on carbonization operating conditions of ANSYS customized kiln for charcoal production from Prosopis juliflora biomass and ANN model prediction for optimized operating conditions - V. Ashok Kumar; K. Muninathan; S. Arivazhagan; N. Monish; M. Venkata Ramanan; Vaddi Seshagiri Rao; Gurunathan Baskar (Fuel, 2023)

Recent insights on tea metabolites, their biosynthesis and chemo-preventing effects: A review - Ramkumar Samynathan; Muthu Thiruvengadam; Shivraj Hariram Nile; Mohammad Ali Shariati; Maksim Rebezov; Raghvendra Kumar Mishra; Baskar Venkidasamy; Sureshkumar Periyasamy; Ill-Min Chung; Mirian Pateiro; José M. Lorenzo (Critical Reviews in Food Science and Nutrition, 2023)

Anti-cancer activity of Hypnea valentiae seaweed loaded gold nanoparticles through EMT signaling pathway in A549 cells - Sandhiya Viswanathan; Thirunavukkarsu Palaniyandi; Dhayan Chand Chellam; Mohammed Fahad Ahmed; Nithin Shoban; M. Pushpakumar; Mugip Rahaman Abdul Wahab; Gomathy Baskar; Maddaly Ravi; Asha Sivaji; Sudhakar Natarajan; Senthil Kumar Sankareswaran (Biochemical Systematics and Ecology, 2023)

The Late Cretaceous-Paleogene Deccan Traps: a Potential Global Heritage Stone Province from India - Gurmeet Kaur; M. F. Makki; R. K. Avasia; Bhaskar Bhusari; Raymond A. Duraiswami; M. K. Pandit; Fareeduddin; R. Baskar; Shashi Kad (Geoheritage, 2019)

Sediment geochemistry with population of recent benthic ostracoda in Palk Bay, southeast coast of India - Sridhar G. D. Sithu; Baskar Kuppusamy; Maniyarasan Subramaniyan; Hussain M. Sheik (Geosciences Journal, 2016)

Biodegradation of toluene vapor in coir based upflow packed bed reactor by Trichoderma asperellum isolate - M. Gopinath; C. Mohanapriya; K. Sivakumar; G. Baskar; C. Muthukumaran; R. Dhanasekar (Environmental Science and Pollution Research, 2016)

Toxic Effects of Couroupita guianensis Against Spodoptera litura (Fabricius) (Lepidoptera: Noctuidae) - K Baskar; S Ignacimuthu; M Jayakumar (Neotropical Entomology, 2015)

Eosinophils as host cells for HIV-1 - B. Conway; P. Baskar; L. J. Bechtel; Joan C. Kaplan; M. S. Hirsch; R. T. Schooley; Stephanie H. Pincus (Archives of Virology, 1992)